Meta-Analysis: Correlation Study Between Science Process Skills and Learning Outcomes - Ahmad Rasyid Ridho Agus (MO.RI Publishing, 2022)
Science process skills are essential for students to obtain and apply knowledge in science education. This meta-analysis aims to estimate the correlation between science process skills and academic achievement in science subjects. The data were collected from 10 journal articles that reported the correlation between science process skills and academic achievement in physics, chemistry, or biology. The results showed a significant positive correlation between science process skills and academic achievement (z = 2.978; p = 0.032; 95% CI [0.039; 0.879]). The effect size of science process skills on academic achievement was moderate (rRE = 0.459). This study suggests that enhancing science process skills can improve students' learning outcomes in science subjects.